2003
DOI: 10.1103/physrevb.67.085316
|View full text |Cite
|
Sign up to set email alerts
|

Full counting statistics of charge transfer in Coulomb blockade systems

Abstract: Full counting statistics ͑FCS͒ of charge transfer in mesoscopic systems has recently become a subject of significant interest, since it proves to reveal an important information about the system which can be hardly assessed by other means. While the previous research mostly addressed the FCS of noninteracting systems, the present paper deals with the FCS in the limit of strong interaction. In this Coulomb blockade limit the electron dynamics is known to be governed by a master equation. We develop a general sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
694
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 450 publications
(712 citation statements)
references
References 27 publications
(56 reference statements)
17
694
0
1
Order By: Relevance
“…The counting statistics of electrons through quantum dots has recently raised considerable theoretical [38,39,40,41,42] as well as experimental [27,43,44,45,46] interest. The single electrons entering and exiting a quantum dot connected to two leads can be measured.…”
Section: Entropy Fluctuations For Electron Transport Trough a Sinmentioning
confidence: 99%
See 1 more Smart Citation
“…The counting statistics of electrons through quantum dots has recently raised considerable theoretical [38,39,40,41,42] as well as experimental [27,43,44,45,46] interest. The single electrons entering and exiting a quantum dot connected to two leads can be measured.…”
Section: Entropy Fluctuations For Electron Transport Trough a Sinmentioning
confidence: 99%
“…In To understand the structure of P (∆S r ), we time integrate (40) and use the fact that in our model the heat current is proportional to the matter current between the ν reservoir and the system I (ν) = I (ν) mat = I (ν) heat /ǫ where…”
Section: Entropy Fluctuations For Electron Transport Trough a Sinmentioning
confidence: 99%
“…5 Spurred by this experimental progress, electron counting statistics ͑ECS͒ in nanosystems has attracted recent theoretical interest both in the noninteracting [6][7][8][9][10][11][12][13][14][15][16] and the Coulomb blockade regimes. 17,18 It has been shown that strong Coulomb interactions suppress large current fluctuations. 17 Double quantum dot ͑DQD͒ systems in parallel geometry [19][20][21][22] and single multilevel quantum dots 23,24 can display interference effects due to the multiple paths that electrons take to cross the junction when Coulomb interaction is present.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 It has been shown that strong Coulomb interactions suppress large current fluctuations. 17 Double quantum dot ͑DQD͒ systems in parallel geometry [19][20][21][22] and single multilevel quantum dots 23,24 can display interference effects due to the multiple paths that electrons take to cross the junction when Coulomb interaction is present. These effects on the average electric current and level population [19][20][21][22][23][24] do not require a magnetic field as in double quantum dot Aharonov-Bohm interferometers.…”
Section: Introductionmentioning
confidence: 99%
“…The full-counting statistics (FCS) formalism [8] as applied to master equations [9] provides a convenient way to calculate transport properties, as well as motivate, in a very physical way, various feedback schemes.…”
Section: Counting Statistics Formalismmentioning
confidence: 99%